Study of the benefits of using exothermic inserts - Baimakanova, Жанаргуль (Рroblems of engineering and professional education, 2023)
This paper proposes the development and implementation of new types of exothermic inserts instead of the profitable part of the castings, and also considers various options for the technology of using exothermic inserts according to alloy grades used on the territory of POLZ LLP.